PENGARUH METODE PERAWATAN TERHADAP KUAT TEKAN BATAKO DAN PAVING BLOCK - Audrey, Bianca Allycia; Kristianto, Anang (Politeknik Negeri Semarang, 2024)
This study was conducted to determine the appropriate maintenance method for bricksand paving blocks, both those that use fly ash and those that do not. The treatmentmethods used in the laboratory were water soaking, wet burlap wrap, plastic wrap,and no treatment with treatment ages of 7 days, 28 days, and 56 days. In the researchconducted at the factory, the treatment methods used were water soaking and notreatment with treatment ages of 8 days, 18 days, 29 days, and 61 days. The highestcompressive strength results in the laboratory reached 24 MPa for specimens withoutfly ash and 18 MPa for specimens with fly ash at 28 days with wet jute wrap treatment.The result of the optimum compressive strength of bricks in the factory reached 16.85MPa for bricks without fly ash and 19.6 MPa for bricks with fly ash at 61 days withthe no-treatment method. The highest average compressive strength of paving blocksin the factory reached 15.28 MPa for paving blocks without fly ash at 61 days withthe no-treatment method, while paving blocks with fly ash reached 19.6 MPa at 18days with the no-treatment method.